2017
DOI: 10.1080/2162402x.2017.1386362
|View full text |Cite
|
Sign up to set email alerts
|

The T cell repertoire in tumors overlaps with pulmonary inflammatory lesions in patients treated with checkpoint inhibitors

Abstract: Cancer immunotherapy with antibodies targeting immune checkpoints such as the PD-1/PD-L1 pathway have emerged as breakthrough treatment for multiple solid tumors with high response rates and durable remissions. Despite the benefit for patients and encouraging safety profile, severe inflammatory reactions are observed in some patients. Such immune-related adverse events (irAEs) frequently lead to temporary or permanent cessation of the treatment and require systemic immunosuppression yet underlying mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 29 publications
4
41
0
1
Order By: Relevance
“…In a report of two patients who died of myocarditis after receiving ipilimumab and nivolumab, similar T cell clones were found in the tumor (melanoma), skeletal muscles, and myocardium from one of the patients [8]. Consistent with this observation is a report of another study of four cases of pneumonitis in patients treated with ICI showing that the TCR repertoires in inflamed lung lesions and tumors overlapped significantly [9]. These observations suggest that cross-reactive T cells against a tumor and a related antigen in normal tissue might be involved in irAE pathogenesis [10].…”
supporting
confidence: 57%
“…In a report of two patients who died of myocarditis after receiving ipilimumab and nivolumab, similar T cell clones were found in the tumor (melanoma), skeletal muscles, and myocardium from one of the patients [8]. Consistent with this observation is a report of another study of four cases of pneumonitis in patients treated with ICI showing that the TCR repertoires in inflamed lung lesions and tumors overlapped significantly [9]. These observations suggest that cross-reactive T cells against a tumor and a related antigen in normal tissue might be involved in irAE pathogenesis [10].…”
supporting
confidence: 57%
“…Laubli et al . also revealed a similarity between T cells in irAEs lesions and tumor infiltrating lymphocytes (TILs) . These findings suggest that ILD reflects the infiltration of T cells with a specificity similar to tumor‐infiltrating T cells.…”
Section: Discussionmentioning
confidence: 61%
“…359 Beyond these nanotechnology-oriented studies, most of the other translational studies on ICD-inducing chemotherapies published over the past 2 years focused on combining ICD induction with immunotherapy or targeted anticancer agents, in keeping with current clinical trends. 360 D'Amico et al (University of Basel, Basel, Switzerland) found that an antibody specific for Erb-B2 receptor tyrosine kinase 2 (ERBB2, also known as HER2) conjugated to an anthracycline derivate exerts potent anticancer effects that depend on cytotoxic T cells in a ERBB2-expressing syngeneic breast cancer model resistant to standard anti-ERBB2 therapy, and that this therapeutic effect can be further enhanced by PD-1 blockage. 205 Fend and collaborators (Gustave Roussy Cancer Campus, Villejuif, France) reported that an engineered oncolytic vaccinia virus, VV WR -TK − RR -Fcu1, can mediate ICD-dependent therapeutic effects (as documented by type I IFN signaling, increased CD8 + T cell infiltration, and improved ratio of effector CD4 + T cells to T REG cells in the tumor microenvironment) that can be potentiated by ICD-inducing chemotherapeutics or immune checkpoint blockers (ICBs).…”
Section: Recent Preclinical Advancesmentioning
confidence: 99%